A plastic shell capacitor and a preparation process thereof

CN122930736APending Publication Date: 2026-10-16DONGGUAN HONGYUAN ELECTRONIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611136426.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]然而,传统的带有金属引线框架的塑壳电容存在固有的局限性:

Benefits of technology

本发明的一种塑壳电容及其制备工艺,通过采用掺杂激光活化添加剂的注塑外形与三维金属化电路的一体化复合结构,实现了电容芯包与壳体内部电路的直接面接触。由于缩短了电流传输路径,从而有效降低了寄生电感和等效串联电阻,迎合高频高速电子设备对低阻抗的严苛需求;同时,无引线框架的设计省去了复杂的机械装配工序,减小了封装体积,有助于提高空间利用率并实现元器件的极限小型化,内壁与外表面的导电层通过化学镀敷与塑壳基体分子级结合,附着力强,杜绝了长期热循环下的接触不良风险,使用寿命长且可靠性高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930736A_ABST
    Figure CN122930736A_ABST
Patent Text Reader

Abstract

The application discloses a plastic shell capacitor and a preparation process thereof, and belongs to the field of capacitor manufacturing and packaging. The plastic shell capacitor comprises a plastic shell body, a capacitor core package contained in the inner cavity of the plastic shell body, and a sealing filler used for sealing the opening of the plastic shell body. The plastic shell body is made of an insulating polymer material doped with a laser-activated additive. A three-dimensional metallized conductive layer is directly combined on the surface and the inner cavity wall of the plastic shell body. The positive and negative lead-out ends of the capacitor core package are respectively in surface contact with the areas of the three-dimensional metallized conductive layer inside the plastic shell body. The three-dimensional metallized conductive layer extends to the outside of the plastic shell body to form external patch pins. The plastic shell body does not have an independent metal lead frame. The special insulating polymer material is combined with the LDS three-dimensional metallized conductive layer, and the traditional metal lead frame is removed, so that an extremely short current path, an extremely low equivalent series resistance and a highly miniaturized packaging structure are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of capacitor manufacturing and packaging technology, specifically to a plastic-cased capacitor and its manufacturing process. Background Technology

[0002] Capacitors are indispensable energy storage and filtering components in modern electronic systems. Currently, most surface-mount solid electrolytic capacitors or tantalum capacitors on the market require the leads of their internal core (element) to be soldered or crimped to external pins via a metal lead frame to complete the electrical connection.

[0003] However, traditional plastic-cased capacitors with metal lead frames have inherent limitations:

[0004] High-frequency impedance: In multi-physical-layer connections (such as core-packed pins / foils connected to lead frames and then extending to external pins), long current paths and complex physical connection nodes introduce high parasitic inductance (ESL) and equivalent series resistance (ESR). In high-frequency applications (such as 5G base stations and high-performance computing), high ESR and ESL lead to a significant increase in the total impedance of capacitors, severely affecting filtering and decoupling performance, and generating additional energy loss and heat.

[0005] To address these issues, the industry has attempted to optimize the lead frame material or minimize the soldering distance. However, as long as the lead frame remains a separate component, it is impossible to fundamentally eliminate the redundant physical connection layers. Furthermore, the lead frame occupies part of the package's internal space, making it difficult to further achieve extreme miniaturization of the capacitor.

[0006] Therefore, how to completely break free from the constraints of traditional metal lead frames while maintaining the insulation protection advantages of plastic-cased capacitors, and revolutionarily shorten the current transmission path to reduce ESR and ESL, is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0007] In order to overcome the shortcomings and deficiencies of the existing technology, the present invention aims to provide a plastic-shell capacitor and its manufacturing process. By combining a special insulating polymer material with an LDS three-dimensional metallized conductive layer, the traditional metal lead frame is eliminated, thereby obtaining an extremely short current path, an extremely low equivalent series resistance, and a highly miniaturized packaging structure.

[0008] This invention is achieved through the following technical solution: In a first aspect, the present invention discloses a plastic-cased capacitor, comprising a plastic-cased body, a capacitor core package housed in the inner cavity of the plastic-cased body, and a sealing filler for closing the opening of the plastic-cased body. The plastic shell body is made of an insulating polymer material doped with laser-activated additives, and a three-dimensional metallized conductive layer is directly bonded to the surface and inner cavity wall of the plastic shell body. The positive and negative leads of the capacitor core are respectively in surface contact with the three-dimensional metallized conductive layer in the region inside the plastic shell body. The three-dimensional metallized conductive layer extends to the outside of the plastic shell body to form external surface mount pins, and there is no independent metal lead frame inside the plastic shell body.

[0009] In conjunction with the first aspect, the three-dimensional metallized conductive layer further includes an inner wall contact pad, a conductive via, and an outer surface mounting pad; the inner wall contact pad is disposed on the inner cavity wall of the plastic shell body and is directly connected to the lead-out end of the capacitor core; the conductive via penetrates the wall thickness of the plastic shell body and electrically connects the inner wall contact pad to the outer surface mounting pad disposed on the outer bottom surface of the plastic shell body.

[0010] In conjunction with the first aspect, the insulating polymer material is any one of liquid crystal polymer, polyamide, or polyphenylene sulfide; the laser-activated additive is an organometallic complex, and the organometallic complex accounts for 3% to 8% of the mass percentage of the insulating polymer material.

[0011] In conjunction with the first aspect, the three-dimensional metallized conductive layer is further described as a multi-layer composite structure, comprising, from the surface of the plastic shell body outwards, a metal crystal nucleus layer formed by laser activation and reduction, a chemically plated copper layer, a chemically plated nickel layer, and an anti-oxidation gold layer or an anti-oxidation tin layer.

[0012] In conjunction with the first aspect, furthermore, the positive and negative leads of the capacitor core are fixedly connected to the inner wall contact pad by conductive silver paste or anisotropic conductive paste, and the connection surface is a planar bonding structure without leads.

[0013] In conjunction with the first aspect, further, the capacitor core is a wound solid aluminum electrolytic capacitor core or a stacked tantalum capacitor core, and the interior of the capacitor core contains a conductive polymer solid electrolyte generated by in-situ polymerization.

[0014] Secondly, the present invention discloses a manufacturing process for a plastic-cased capacitor, which includes the following steps: S100. Inject insulating polymer material particles doped with the laser activation additive into a mold, and injection mold at a preset temperature to obtain the plastic shell body with an inner cavity and a reserved through hole; S200. Using a laser beam to scan and irradiate the inner wall of the plastic shell body, the inner wall of the through hole, and the outer bottom surface according to a preset three-dimensional circuit path, so that the surface layer of the insulating polymer material in the irradiated area undergoes a physicochemical reaction and precipitates metal crystal nuclei. S300. The activated plastic shell body is placed in a chemical plating solution, and the precipitated metal crystal nuclei are used as catalysts to deposit metal, and the three-dimensional metallized conductive layer is grown on the preset three-dimensional circuit path. S400. Apply conductive adhesive to the inner wall contact pad inside the plastic shell body, push the capacitor core into the inner cavity so that its positive and negative leads are in contact with the conductive adhesive, and then heat to cure. S500. Inject fluid-like insulating resin into the opening of the plastic shell body, and degas and cure it under vacuum to form the sealing filler to complete the final encapsulation.

[0015] In conjunction with the second aspect, further, in step S200, the laser beam is an infrared laser with a wavelength of 1064nm or an ultraviolet laser with a wavelength of 355nm; the laser irradiation power is 5W~20W, and the laser scanning speed is controlled between 1000mm / s and 4000mm / s.

[0016] In conjunction with the second aspect, further, in step S300, the chemical plating process sequentially performs chemical copper plating, chemical nickel plating, and chemical gold / tin plating processes; the total thickness of the formed three-dimensional metallized conductive layer is controlled between 15μm and 40μm.

[0017] In conjunction with the second aspect, further, in step S400, the heating and curing adopts a stepped temperature rise curve: first, pre-curing is carried out at an ambient temperature of 80℃~100℃ for 15~30 minutes to evaporate the solvent, and then the temperature is raised to an ambient temperature of 150℃~170℃ and held for 1~2 hours to achieve complete cross-linking and curing.

[0018] The beneficial effects of this invention are: This invention discloses a plastic-shell capacitor and its manufacturing process. By employing an integrated composite structure of an injection-molded shape doped with laser-activated additives and a three-dimensional metallized circuit, direct surface contact between the capacitor core and the internal circuitry of the casing is achieved. This shortens the current transmission path, effectively reducing parasitic inductance and equivalent series resistance, meeting the stringent low-impedance requirements of high-frequency, high-speed electronic devices. Simultaneously, the leadless design eliminates complex mechanical assembly processes, reduces package size, improves space utilization, and achieves extreme miniaturization of components. The conductive layers on the inner wall and outer surface are chemically plated and bonded to the plastic shell substrate at the molecular level, resulting in strong adhesion, eliminating the risk of poor contact under long-term thermal cycling, and ensuring a long service life and high reliability. Attached Figure Description

[0019] The present invention will be further described with reference to the accompanying drawings, but the embodiments in the drawings do not constitute any limitation on the present invention. For those skilled in the art, other drawings can be obtained based on the following drawings without creative effort.

[0020] Figure 1 This is a schematic diagram of the structure of a plastic-cased capacitor in one embodiment of the present invention.

[0021] Figure 2 This is a process flow diagram of the manufacturing process of a plastic-cased capacitor according to one embodiment of the present invention.

[0022] Figure Labels Plastic-cased capacitor--10, plastic-cased body--100, inner wall contact pad--201, conductive via--202, outer surface mounting pad--203, conductive adhesive--300, capacitor core--400, positive lead--401, negative lead--402, sealing filler--500. Detailed Implementation

[0023] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0024] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.

[0025] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0026] Example 1 like Figure 1 As shown, this embodiment discloses a plastic-cased capacitor 10, which aims to solve the problems of excessively high high-frequency impedance and difficulty in further miniaturization caused by the use of metal lead frames in traditional capacitors.

[0027] Specifically, the plastic-cased capacitor 10 includes a plastic-cased body 100, a capacitor core 400 housed in the inner cavity of the plastic-cased body 100, and a sealing filler 500 for closing the opening of the plastic-cased body 100.

[0028] In traditional molded capacitor packages (10), the current through the capacitor core (400) must pass through a complex process involving the core leads, solder layers, metal lead frame, and external pins. This significantly increases parasitic inductance (ESL) and equivalent series resistance (ESR). To overcome this physical limitation, the molded casing (100) in this embodiment is made of a specially formulated material, namely an insulating polymer material doped with laser-activated additives. This special material maintains excellent insulation and structural strength while possessing the ability to be locally metallized using laser direct forming (LDS) technology.

[0029] Based on the aforementioned special plastic shell material, in this embodiment, a three-dimensional metallized conductive layer is directly bonded to the surface and inner wall of the plastic shell body 100. This conductive layer is no longer a physical metal component independent of the shell, but rather a metal circuit that is grown at the molecular level and firmly attached to the surface of the plastic shell body 100 through laser activation and chemical plating processes.

[0030] In terms of internal connection structure, the capacitor core 400 is directly pushed into the inner cavity of the plastic shell body 100, and its positive lead 401 and negative lead 402 respectively achieve surface contact and conduction with the three-dimensional metallized conductive layer located in the inner region of the plastic shell body 100. Surface contact means that the end face of the core is directly attached to the metallized layer of the inner cavity, completely eliminating traditional spot welding, wire welding, or mechanical crimping processes. This large-area direct surface contact not only allows the current to flow out of the core with the shortest straight distance, reducing internal contact resistance, but also avoids reliability problems caused by stress concentration at the solder joints.

[0031] In the external lead structure, the three-dimensional metallized conductive layer extends continuously along the inner wall of the plastic shell 100 to the outer surface of the plastic shell 100, directly forming external surface mount pins on the bottom or side of the capacitor. Since the inner wall conductive layer and the external pins are continuous metal layers generated in the same process, without any intermediate interface, efficient and lossless current transmission is achieved.

[0032] Finally, after the capacitor core package 400 is assembled in place, the opening of the plastic shell body 100 is filled with sealing filler 500. The sealing filler 500 completely isolates the inner cavity from the external environment, preventing moisture, oxygen, etc. from entering and causing the core package to become damp or the internal circuit to oxidize. It also plays a role in mechanically fixing the capacitor core package 400 and in buffering and shock absorption.

[0033] As a preferred embodiment, this embodiment further defines the specific topology and electrical connection path of the three-dimensional metallized conductive layer. The three-dimensional metallized conductive layer is specifically divided into three functional regions: an inner wall contact pad 201, a conductive via 202, and an outer surface mounting pad 203. These three regions are generated during the fabrication process through continuous laser activation and chemical plating processes, forming a seamlessly connected metallic conductive whole.

[0034] Specifically, the inner wall contact pad 201 is disposed on the inner cavity wall of the plastic shell body 100. In actual engineering design, the geometry and coverage area of ​​the inner wall contact pad 201 match the end face characteristics (i.e., positive and negative electrode surfaces) of the capacitor core 400, and the inner wall contact pad 201 is directly connected to the end face of the capacitor core 400. This planar bonding structure replaces the traditional point welding or pin crimping, enabling the charging and discharging current to be uniformly distributed on the end face of the capacitor core 400, significantly reducing the contact resistance of the connection interface, effectively suppressing the hot spot effect caused by local high current density, and improving the high current carrying capacity of the device.

[0035] To achieve short-path transmission of electrical signals inside and outside the cavity, the conductive via 202 penetrates the wall thickness of the plastic housing body 100. In this structure, the conductive via 202 constitutes the most direct physical bridge between the internal circuit and the external packaging interface. Compared with the traditional edge-wrapping method of extending conductive lines upward along the inner wall of the plastic housing and then routing them over the edge of the opening to the outer bottom surface, the through-hole conductive via 202 design significantly reduces the physical distance for carrier transmission. The dense metallized plating on the inner wall of the via not only structurally reduces parasitic inductance under high-frequency operation, but also endows the channel with excellent thermal conductivity. When the capacitor is operating under high-frequency ripple current, the Joule heat generated inside the core can be quickly conducted to the external printed circuit board through the metal layer of the conductive via 202, improving the inherent low thermal conductivity of the plastic housing assembly and enhancing the overall heat dissipation efficiency.

[0036] Regarding the external interface, the conductive via 202 enables a low-impedance electrical connection between the inner wall contact pad 201 and the outer surface mount pad 203 located on the bottom surface of the plastic housing 100. The outer surface mount pad 203 serves as the physical interface for the final surface mount technology (SMT) soldering of the capacitor to the external printed circuit board, and is directly formed on the bottom outer surface of the plastic housing 100. The size, spacing, and layout of the outer surface mount pad 203 can be customized according to the pad packaging specifications of standard surface mount components (such as EIA standards) to meet the requirements of high-reliability surface mount processing such as automated reflow soldering.

[0037] The inner wall contact pad 201, conductive via 202, and outer surface mounting pad 203 work together to construct a compact, low-impedance three-dimensional conductive network on the insulating plastic shell substrate. This structural design, by eliminating the independent metal lead frame, achieves efficient and low-loss transmission of energy and electrical signals inside and outside the cavity, thereby improving the electrical performance and structural stability of the plastic shell capacitor 10 in high-frequency, high-speed electronic systems.

[0038] As a preferred embodiment, this embodiment further specifies the substrate type of the plastic shell body 100 and the specific composition and ratio of the laser activation additive.

[0039] Specifically, the insulating polymer material is any one of liquid crystal polymer (LCP), polyamide (PA), or polyphenylene sulfide (PPS). The selection of these special engineering plastics as the shell matrix is ​​primarily based on their excellent comprehensive physical and chemical properties exhibited in the field of electronic component packaging. LCP has a low coefficient of thermal expansion and high flowability, meeting the requirements for thin-walled and precision injection molding of the shell, and can withstand the high temperatures of SMT reflow soldering above 260°C without warping. PA possesses good mechanical toughness and high compatibility with LDS processes, facilitating metal layer adhesion. PPS exhibits outstanding chemical corrosion resistance, low water absorption, and intrinsic flame retardant properties, providing reliable environmental isolation and protection for the internal capacitor core 400.

[0040] To achieve laser direct molding, the laser-activated additive employs an organometallic complex. This additive is uniformly dispersed within the insulating polymer matrix during the injection molding stage, maintaining electrical insulation under normal temperature and operating conditions without compromising the original dielectric properties of the plastic shell 100. Its working principle is as follows: when a specific area of ​​the shell is irradiated by a laser of a preset wavelength and energy, the surface polymer matrix undergoes localized ablation, while the exposed organometallic complex undergoes photochemical or thermochemical decomposition under the high energy of the laser. The organic ligands in the complex break down and volatilize, reducing the core metal ions and precipitating in situ catalytically active micro / nano-scale metal nuclei (such as copper or palladium nuclei). These metal nuclei, anchored to the roughened plastic surface, will act as highly active catalysts in subsequent chemical plating processes, guiding the targeted deposition of free metal ions, thereby achieving a strong molecular-scale bond between the metal layer and the plastic substrate.

[0041] Furthermore, this embodiment limits the mass percentage of the organometallic complex in the insulating polymer material to 3%~8%. This numerical range is an optimized range determined through thorough process validation, aimed at balancing the film-forming quality of the plastic shell with the mechanical / electrical properties of the bulk material. When the mass percentage of the organometallic complex is less than 3%, the density of metal nuclei precipitated on the surface of the plastic shell after laser activation is insufficient. This will lead to a significant reduction in the deposition rate of the subsequent chemical plating layer, poor plating continuity, and a tendency for microscopic pores or edge "missing plating" phenomena to occur. Consequently, the overall adhesion of the three-dimensional metallized conductive layer decreases, the internal resistance increases, and it cannot meet the low impedance requirements of high-frequency circuits.

[0042] When the mass percentage of organometallic complexes exceeds 8%, excessive doping of inorganic or organometallic particles can lead to agglomeration within the polymer matrix, disrupting the continuity of the polymer molecular chains. This not only significantly degrades the mechanical properties of the plastic shell 100 (such as impact strength and tensile elongation at break), making it prone to brittle cracking during assembly or high / low temperature thermal cycling; but also, excessively high concentrations of metal additives can reduce the volume resistivity and breakdown voltage of adjacent insulating regions, increasing the risk of increased leakage current under high voltage.

[0043] Therefore, by controlling the mass percentage of the laser-activated additive between 3% and 8%, the high density and strong bonding of the metal circuit after laser activation are ensured, while maintaining the original high strength and high insulation properties of the polymer substrate, thus providing a basic material guarantee for the overall reliability of the plastic-shell capacitor 10.

[0044] As a preferred embodiment, this embodiment further defines the microstructure of the three-dimensional metallized conductive layer. To balance high adhesion, high conductivity, and excellent welding reliability, the three-dimensional metallized conductive layer is designed as a multi-layer composite structure, comprising, from the surface of the plastic shell body 100 outwards, a metal nucleus layer formed by laser activation and reduction, a chemically plated copper layer, a chemically plated nickel layer, and an anti-oxidation gold layer or an anti-oxidation tin layer.

[0045] Specifically, each layer plays the following role in three-dimensional circuit interconnection: The metal nucleus layer, serving as the foundational structure of the entire conductive network, is generated by scanning the surface of the plastic shell body 100 with a specific wavelength laser along a pre-defined three-dimensional circuit path. This process causes the organometallic complexes in the polymer matrix to decompose and be reduced in situ, producing micro- and nano-sized metal particles (such as palladium or copper nuclei). During laser ablation, a micro-rough structure forms on the surface of the plastic matrix. The generated metal nuclei not only provide highly active catalytic sites for subsequent chemical plating but also form an effective mechanical anchoring effect with the plastic matrix through this micro-rough surface. This fundamentally ensures the bonding force between the metallized conductive layer and the plastic substrate, preventing the metal layer from blistering or peeling off in environments of thermal expansion and contraction.

[0046] The electroless copper plating layer is a basic conductive layer formed through targeted growth via a chemical precipitation reaction guided by the catalysis of metal crystal nuclei. Due to the excellent volumetric conductivity of pure copper, this layer serves as the main current-carrying channel for the entire three-dimensional metallized conductive layer, undertaking the majority of the charge and discharge current transmission. The high density and continuity of the electroless copper plating layer can significantly reduce the DC resistance and high-frequency AC impedance of the conductive path, making it a key functional layer for achieving the extremely low equivalent series resistance of this invention.

[0047] The electroless nickel plating layer tightly covers the copper plating layer, primarily acting as a barrier layer in the composite structure. On one hand, the highly dense nickel layer effectively isolates oxygen and moisture from the external environment, preventing oxidation or corrosion of the inner pure copper layer and thus reducing its conductivity. On the other hand, during the curing and assembly of the capacitor core 400 or the final SMT reflow soldering process, the nickel layer effectively blocks the abnormal diffusion of copper atoms to the surface metal, inhibiting the excessive growth of undesirable intermetallic compounds (IMCs), thereby maintaining the stability of the conductive interface under long-term thermomechanical stress.

[0048] The anti-oxidation gold layer or anti-oxidation tin layer is located on the outermost surface of the composite structure, mainly used to provide a stable and reliable contact interface and excellent solderability. If the outer layer uses an anti-oxidation gold layer (i.e., chemical nickel plating process ENIG), it has the characteristics of strong corrosion resistance and low surface contact resistance, which is very conducive to the formation of a low-impedance surface contact connection between the inner wall contact pad 201 and the lead of the capacitor core 400 through conductive adhesive 300 (such as conductive silver paste or ACF); if the outer layer uses an anti-oxidation tin layer, since the tin layer has good metallurgical compatibility with conventional lead-free solder in the electronics industry, it can ensure that the external surface mount pins form a reflow solder joint with good wettability and high mechanical strength on the PCB board.

[0049] The aforementioned multi-layer composite structure, through a reasonable division of labor between bottom-layer anchoring, middle-layer current carrying, barrier protection, and surface welding, constructs a low-loss, highly reliable three-dimensional electrical interconnection interface, further consolidating the technical feasibility and long-term durability of the leadless frame design.

[0050] As a preferred embodiment, this embodiment further defines the physical and electrical connection between the capacitor core 400 and the internal circuitry of the housing to ensure structural stability and low impedance characteristics after eliminating the lead frame.

[0051] Specifically, the positive terminal 401 and the negative terminal 402 of the capacitor core 400 are fixedly connected to the inner wall contact pad 201 by conductive silver paste or anisotropic conductive paste 300 (ACF).

[0052] In terms of material selection, conductive silver paste or anisotropic conductive adhesive 300 replaces the traditional metal welding process, offering significant technical advantages. Conductive silver paste typically uses a special resin as a matrix and micron- or nano-sized silver particles as conductive fillers. Its curing temperature is usually much lower than traditional tin soldering or laser spot welding processes (for example, complete cross-linking and curing can be achieved at around 150℃). This relatively low-temperature connection method effectively avoids the deformation risk to the plastic shell body 100 caused by high-temperature thermal shock, while also protecting the temperature-sensitive solid electrolyte (such as conductive polymer) inside the capacitor core 400 from thermal degradation. The conductive network formed by high-density silver particles in the resin matrix provides an excellent low-impedance path for high-frequency, high-current applications. Using anisotropic conductive adhesive 300 provides high conductivity in the vertical (Z-axis) direction while utilizing its resin matrix to provide good environmental sealing and buffer energy absorption, further improving the assembly yield under small package sizes.

[0053] More importantly, the connection surface is designed as a pinless planar bonding structure.

[0054] In traditional capacitor packaging, the connection points between the leads (such as pins or lead foils) of the core and the lead frame are often small local solder joints or crimping points. This point-like or line-like connection method not only has a small effective conductive cross-sectional area, but also easily generates severe stress concentration at the solder joint during thermal expansion and contraction, leading to poor soldering or breakage after long-term use.

[0055] The leadless planar bonding structure used in this embodiment allows the end face of the capacitor core 400 to be directly and smoothly attached to the three-dimensional metallized contact pad on the inner wall of the plastic shell using a layer of conductive adhesive 300. This surface-to-surface contact structure brings dual technical benefits: In terms of electrical performance, planar bonding significantly increases the effective physical cross-sectional area of ​​the conductive interface, allowing the charging and discharging current to flow vertically from the end face of the core package into the contact pad evenly, greatly reducing the interface contact resistance. This is an important microscopic guarantee for achieving low equivalent series resistance in capacitors.

[0056] In terms of mechanical reliability, the large-area adhesive bonding layer acts as a uniform stress buffer, which can evenly distribute the shear stress generated by the difference in the thermal expansion coefficient of the materials during the operation of the capacitor, or the impact force generated by external mechanical vibration, to the entire end face. This effectively avoids interface peeling or fatigue failure caused by local stress concentration, and significantly improves the overall reliability of the device under harsh environments (such as high-frequency vibration and severe thermal cycling).

[0057] As a preferred embodiment, this embodiment further defines the specific structural type of the capacitor core 400 and the composition and formation process of its internal electrolyte.

[0058] Specifically, the capacitor core 400 is a wound solid aluminum electrolytic capacitor core 400 or a stacked tantalum capacitor core 400.

[0059] When a wound solid aluminum electrolytic capacitor core package 400 is selected, it is typically formed by rolling and flattening an anode aluminum foil, a cathode aluminum foil, and insulating paper sandwiched between them. This structure can provide a large dielectric surface area within a limited volume, thereby achieving a high nominal capacitance. When a multilayer tantalum capacitor core package 400 is selected, it is mainly composed of a porous dielectric formed by pressing tantalum powder and sintering it at high temperature, featuring small size and high specific capacitance. The geometric shape of both core packages can achieve a high-density spatial match with the internal cavity of the plastic shell body 100, and both have good high-temperature resistance characteristics, which can adapt to the subsequent surface mount technology reflow soldering process.

[0060] Furthermore, the capacitor core 400 contains an in-situ polymer solid electrolyte generated by polymerization.

[0061] In traditional liquid electrolytic capacitors, the liquid electrolyte is prone to evaporation, drying out, and even gas generation leading to leakage under long-term operation or high-temperature environments. This not only causes a sharp increase in the equivalent series resistance of the capacitor but also places extremely high demands on the sealing performance of the plastic casing. To overcome these physical defects, this embodiment uses a conductive polymer (such as poly(3,4-ethylenedioxythiophene), i.e., PEDOT) as the solid electrolyte. The use of a solid electrolyte fundamentally eliminates the risk of liquid leakage and drying failure, improving the stability of the plastic-cased capacitor 10 under long-term thermal cycling conditions.

[0062] More importantly, this conductive polymer is generated through an in-situ polymerization process. In the preparation stage, liquid monomers (such as EDOT) and an oxidant / dopant solution are first immersed into the unsealed capacitor core 400. Because the monomer mixture has extremely low viscosity before polymerization, it can fully penetrate deep into the micron-sized etched pores of the anode foil or the nanoscale porous structure of the tantalum block through capillary action. Subsequently, under specific temperature conditions, the monomers undergo in-situ chemical polymerization within the micropores, cross-linking to form a solid polymer network with high electrical conductivity.

[0063] Through in-situ polymerization, the generated conductive polymer can form a highly dense and widely covered microscopic physical bonding interface with a porous dielectric oxide film (such as an alumina layer or tantalum oxide layer). This deep microscopic penetration combined with the high conductivity material significantly reduces the charge transfer impedance between the internal dielectric layer and the cathode of the capacitor. This low internal impedance characteristic, together with the solution of this embodiment, constructs a low-loss current path throughout the entire link from the microscopic dielectric interface to the macroscopic external pins, thereby ensuring that the plastic-cased capacitor 10 exhibits excellent filtering performance and high ripple current tolerance in high-frequency, high-voltage circuits.

[0064] Example 2 Based on the above structural design of the plastic-cased capacitor 10, this embodiment also provides a manufacturing process for the plastic-cased capacitor 10. For example... Figure 2 As shown, this process achieves leadless three-dimensional circuit interconnection and packaging through a series of specific steps, including the following steps: S100. Injection molding: First, insulating polymer material particles (such as LCP, PA, or PPS) doped with a specified proportion of organometallic complex (as a laser activation additive) are added to an injection molding machine and melted at a preset temperature. The melt is then injected under high pressure into a mold with a specific geometric cavity. After cooling and demolding, a plastic shell body 100 with an internal cavity and pre-reserved conductive through-holes 202 is obtained. This step establishes the overall external dimensional outline and internal assembly space of the capacitor, and the insulating matrix is ​​now uniformly distributed with metal activating agents.

[0065] S200. Laser activation: The injection-molded plastic shell body 100 is fixed on a laser processing platform. A laser beam is used to continuously scan and irradiate the inner cavity wall, the inner wall of the reserved through hole, and the outer bottom surface of the plastic shell body 100 according to a three-dimensional circuit path pre-designed in the control software. Under the action of high-energy laser photons, the surface layer of the insulating polymer material in the irradiated area undergoes microscopic ablation and roughening. At the same time, the organometallic complexes doped therein undergo physicochemical reactions and decompose, thereby precipitating catalytically active micro- and nano-sized metal nuclei in situ on the surface of the irradiation path.

[0066] S300. Chemical plating: After being cleaned following laser activation treatment, the plastic shell body 100 is placed in a specific chemical plating solution. During the chemical plating process, using the metal nuclei precipitated in step S200 as a catalyst, the free metal ions in the plating solution undergo an autocatalytic reduction reaction and are targeted and deposited on the surface of the nuclei. As the reaction proceeds, the metal coating gradually grows and interconnects along the preset three-dimensional circuit path irradiated by the laser, ultimately forming a dense and strongly adherent three-dimensional metallized conductive layer. Since the areas not irradiated by the laser do not have metal nuclei, the metal layer will not deposit in non-circuit areas, thus achieving selective metallization on the insulating substrate.

[0067] S400. Surface contact assembly: A measured amount of conductive adhesive 300 is applied to the surface of the three-dimensional metallized conductive layer (specifically, the inner wall contact pad 201) within the inner cavity of the plastic shell body 100 using dispensing or screen printing. Subsequently, using automated equipment, the impregnated or cured capacitor core 400 is precisely pushed into the inner cavity of the plastic shell, ensuring that the end faces of its positive lead 401 and negative lead 402 fully adhere to the conductive adhesive 300 on the corresponding inner wall contact pad 201, forming a planar contact structure. After assembly, the entire structure is placed in a heating device for heat curing, causing the conductive adhesive 300 to undergo a cross-linking reaction, thereby achieving a firm physical fixation and low-impedance electrical connection between the capacitor core 400 and the internal circuitry of the shell.

[0068] S500. Vacuum Encapsulation: The semi-finished product, with its core assembly and electrical connections completed, is transferred into a vacuum potting apparatus. An appropriate amount of fluid insulating resin (such as low-stress epoxy resin) is injected into the opening of the plastic shell 100. Subsequently, a degassing process is performed under a set vacuum environment to remove residual micro-bubbles from the resin interior and the gap between the core and the shell. Finally, the resin is cross-linked and hardened through a heating or room-temperature curing process to form a dense sealing filler 500. The sealing filler 500 not only seals the shell opening, isolating the internal core from moisture and oxygen in the external environment, but also provides overall encapsulation and mechanical support for the internal components, completing the final encapsulation of the plastic shell capacitor 10.

[0069] The fabrication process provided in this embodiment combines polymer injection molding technology with LDS three-dimensional interconnect technology, replacing the traditional stamping, bending, and welding processes of the metal lead frame with in-situ metallization on the surface of the plastic shell. This process not only effectively shortens the current transmission path inside the device but also significantly simplifies the overall production process, improves assembly yield, and is suitable for large-scale, automated manufacturing of low-ESR high-frequency capacitors.

[0070] As a preferred embodiment, this embodiment further specifies the laser activation process in step S200 in detail.

[0071] Specifically, the laser beam uses an infrared laser with a wavelength of 1064nm or an ultraviolet laser with a wavelength of 355nm; during the activation process, the laser irradiation power is set at... Between, the laser scanning speed is controlled at The choice of different wavelengths is mainly based on the absorption spectral characteristics of insulating polymer materials and metal complexes. 355nm ultraviolet laser has higher single-photon energy, tends to cause photochemical bond breaking during cold processing, and has a small edge heat-affected zone; while 1064nm infrared laser is mainly based on thermochemical effects and has a large processing depth.

[0072] To ensure that dense and uniform metal nuclei are excited when the laser sweeps across the surface of a complex three-dimensional plastic shell (including flat surfaces, dead corners of internal cavities, and conductive vias 202), the laser processing system in this embodiment incorporates a thermodynamic nucleation control algorithm. This algorithm precisely controls the reduction rate of organometallic complexes in the polymer matrix through a nonlinear mapping of laser power and scanning speed.

[0073] The control algorithm comprises a two-level computational model: an offline activation rate prediction model and an online real-time power compensation model.

[0074] 1. Offline activation rate prediction model (higher-order integral and exponential function) Laser-induced metal nucleus precipitation is a thermochemical kinetic process driven by a transient temperature field. The nucleus precipitation rate (activation rate) at any point on the surface of an insulating polymer material under laser irradiation is shown. Following the modified Arrhenius integral equation:

[0075] Among them, the transient temperature field on the material surface Based on the Fourier differential equation of heat conduction of the Gaussian moving heat source, the following is derived:

[0076] in, Set the power for the laser, with a range of values. It is preset according to processing requirements; The laser scanning speed ranges from 1000mm / s to 4000mm / s and is preset according to processing requirements. The pre-exponential factor for the reduction reaction of metal complexes was obtained through thermogravimetric analysis and differential scanning calorimetry of the materials. The activation energy for the cleavage and reduction of organometallic complexes is typically taken in the range of [value missing]. It is determined by the chemical properties of the specific additives; The ideal gas constant is a fixed value. ; The initial ambient temperature is taken as room temperature. ; The absorption rate of the insulating polymer material to laser light of a specific wavelength (1064 nm or 355 nm) is given, with a value range of [value missing]. Measurements were taken using a UV-Vis-NIR spectrophotometer. These are the material's density, specific heat capacity, and thermal diffusivity, respectively. These physical property constants are provided by the material supplier or can be found in the material handbook.

[0077] 2. Online Real-Time Power Compensation Model In actual 3D circuit routing, the scanning speed of the galvanometer scanner when passing through right angles, vias, or curved surfaces is... Abrupt acceleration and deceleration will inevitably occur. This is to ensure the energy density and final activation rate at each point along the path. The laser control system maintains a constant power level and modulates the power in real time based on the instantaneous velocity.

[0078] in, The reference power and reference speed are determined through an offline model. Let be the instantaneous velocity of the galvanometer at the current moment. This refers to the command power output by the system in real time.

[0079] The derivation of the above formula is based on the coupling of heat transfer (e.g., transient integral of a Gaussian moving heat source) with chemical kinetics (e.g., first-order reaction kinetics and the Arrhenius equation).

[0080] In terms of experimental verification, different methods were selected during the research and development process. The parameter combination was used to prototype the plastic shell body 100, and then the cross-section of the activated region was observed using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Experimental data show that when The theoretical activation rate calculated by substituting the parameters into the offline model When the abundance of surface metal elements shown by EDS drops sharply below a preset threshold (e.g., 75%), subsequent electroless plating is highly prone to incomplete plating. However, using an online power compensation formula... After corner area correction, the excessive ablation phenomenon at the corner of the trace disappeared, and the variance of the metal nucleus density of the entire three-dimensional circuit path was reduced by more than 80%, proving the reliability and process compatibility of the algorithm.

[0081] In practice, the two algorithms mentioned above adopt a collaborative operation mode of offline calculation + online real-time control.

[0082] In offline computation, the transient temperature field and the activation rate integral equation Involving complex transcendental equations and high-order numerical integrals, the computational cost is enormous. This operation is performed offline by CAM software running on an industrial computer (host computer) before production. The host computer uses methods such as the Runge-Kutta method to solve the integral and generate the optimal... Reference parameter set and process control window.

[0083] In online real-time control and equipment execution, the formula For low-latency algebraic operations, the implementation device is a field-programmable gate array (FPGA) or digital signal processor (DSP) control board inside the laser marking system. During processing in step S200, the FPGA reads the instantaneous position in real time at a sub-microsecond sampling rate using the photoelectric encoder of the XY galvanometer motor and obtains the result by time differentiation. The target power is then calculated by substituting the result into the square root compensation formula, and finally converted into pulse width modulation (PWM) or analog voltage signal to directly control the laser pump source. This hardware architecture ensures that the processing speed is much higher than the laser sweeping speed, thus supporting the physical implementation of this control algorithm.

[0084] As a preferred embodiment, this embodiment further specifies in detail the specific process flow of chemical plating in step S300 and the thickness parameters and control mechanism of the three-dimensional metallized conductive layer.

[0085] Specifically, the electroless plating process sequentially involves electroless copper plating, electroless nickel plating, and electroless gold / tin plating. This sequential process forms a composite conductive network: the copper plating layer acts as the main conductor, the nickel plating layer acts as a barrier layer to prevent the diffusion of copper atoms, and the gold / tin plating layer acts as the outermost layer for oxidation protection and solderability.

[0086] This embodiment strictly specifies that the total thickness of the formed three-dimensional metallized conductive layer is controlled within a certain range. The thickness range is based on a comprehensive consideration of the high-frequency skin effect and mechanical stress: if the thickness is less than 15... If the cross-sectional area of ​​the metal layer is insufficient, the ESR will increase significantly under high-frequency operating conditions, failing to meet the requirements of high-current transmission. Furthermore, the thin metal layer is prone to electromigration fracture during thermal cycling; if the thickness exceeds 40... Not only will it significantly increase the manufacturing cost and time of chemical plating, but the excessively grown metal layer will also accumulate huge internal stress on the surface of the plastic shell substrate, leading to a decrease in adhesion and even the risk of peeling and detachment of the plating.

[0087] To overcome the impact of plating solution concentration decay on coating thickness uniformity in mass production, and to accurately target... To determine the target thickness window, the chemical plating system in this embodiment incorporates a real-time thickness control algorithm based on the coupling of mass transfer and reaction kinetics.

[0088] In electroless plating, the metal deposition rate is limited by the interfacial reaction kinetics at the surface and the mass transport (diffusion) rate within the plating bath. The deposition thickness is not only time-dependent but also undergoes nonlinear changes with real-time fluctuations in the plating bath concentration and temperature. This system, based on the steady-state diffusion approximation and the Arrhenius reaction equation, uses the following high-order integral equation to calculate the real-time deposition thickness. :

[0089] in, The current integration time The total accumulated thickness of the metal coating, the target value is between; Let be the molar mass of the deposited metal, and for copper, take the value of . The physical property constants; The number of electrons transferred in the reduction reaction is typically 2 for chemical copper plating; Let be the Faraday constant, and let its value be . The physical constants; The theoretical density of the deposited metal layer is given, with copper valued at 8.96. ; To determine the real-time bulk concentration of the main salt metal ion, the value range is typically controlled within a certain range. The data are obtained in real time using an online UV-Vis spectrophotometer or automatic potentiometric titrator immersed in the plating bath. The intrinsic reaction rate constant of the surface is determined by the specific bath solution formulation and is obtained through offline calibration using prior potentiodynamic polarization curve experiments. The activation energy for the deposition reaction depends on the activity of the reducing agent (such as formaldehyde or sodium hypophosphite), and is typically found in the range [missing information]. The values ​​were determined through isothermal deposition experiments at different temperatures. The ideal gas constant is 8.314. ; This refers to the absolute temperature of the plating solution in real time, typically within the range of [value missing]. The data is collected in real time by PT100 high-precision resistance thermal sensors arranged in different areas of the bath solution; The thickness of the solution diffusion boundary layer is 10. This parameter is related to the air stirring rate or the flow rate of the circulating pump in the plating tank, and is estimated by mapping using empirical formulas for the boundary layer in fluid mechanics or data from online flow meters. The diffusion coefficient of the metal ion in solution is given; it can be determined by consulting an electrochemical handbook or by cyclic voltammetry. The above algorithm formula is derived by coupling Fick's first diffusion law with the reaction kinetic equation. In electroless plating, the diffusion flux of metal ions must equal the chemical consumption flux of the surface. Due to the large volume of industrial-grade electroless plating tanks, the concentration of the main salt in the bath increases with continuous production. It will gradually decay, and the accumulation of byproducts will cause a slight change in the activation energy of the reaction. Traditional timed lifting methods cannot cope with this nonlinear decay.

[0090] Experimental verification shows that, without this algorithm, due to bath aging, the difference in conductive layer thickness between the first and last two ends of the same batch of plastic-shell capacitors exceeds 8 mm. This resulted in poor ESR consistency. After introducing this integral control algorithm, the system dynamically compensated for concentration and temperature fluctuations through real-time integration, ensuring that the coating thickness strictly converged to 25 mm after 500 consecutive batches of production. Near the process center value, the thickness tolerance is compressed to ±1.5. Within this period, the engineering effectiveness of the model in addressing thickness runaway caused by plating solution degradation was verified.

[0091] Specifically, the algorithm is an online real-time control operation.

[0092] In the hardware architecture of this embodiment, the algorithm is executed by a distributed control system (DCS) or a high-performance programmable logic controller (PLC). Its equipment collaborative control is based on the following: Data Acquisition: After production starts, the temperature sensor and spectrophotometer integrated inside the tank send the current data to the PLC every set period (e.g., 100 milliseconds). and data.

[0093] Numerical integration and chemical dosing compensation: The high-speed microprocessor inside the PLC uses the trapezoidal rule or Simpson's rule to perform real-time discretization and integration of the above equations, updating the current estimated thickness. Meanwhile, when the system detects that the precondition (such as concentration) in the integrand is decreasing too rapidly, the PLC will synchronously output an analog signal to the automatic dosing pump to accurately replenish copper sulfate or formaldehyde stock solution.

[0094] Closed-loop lifting execution: The communication interface of the automated hoist is connected to the same industrial bus. When the cumulative thickness integral value of the PLC's internal algorithm... When the target thickness (e.g., 25 μm) is reached, the system immediately issues an interrupt command; the trolley responds, automatically removing the fixture carrying the plastic-cased capacitor 10 from the chemical plating tank and transferring it to the next water washing process. This ensures, through the structure and control chain, that the thickness of the three-dimensional metallized conductive layer fully complies with the standards defined in the claims.

[0095] As a preferred embodiment, this embodiment further specifies in detail the surface contact heating and curing process of the conductive adhesive 300 in step S400 and the thermodynamic control mechanism of its underlying layer.

[0096] Specifically, the heating and curing process employs a stepped temperature rise curve: firstly in... Performed at ambient temperature Pre-curing solvent evaporates within minutes, then the temperature is raised to [temperature missing]. Insulation at ambient temperature Complete cross-linking and curing can be achieved within hours.

[0097] In leadless frame surface contact assembly structures, conductive silver paste or anisotropic conductive adhesive 300 (ACF) not only serves as a physical bond but also acts as the sole charge transfer channel between the internal capacitor core 400 and the three-dimensional circuitry on the inner wall of the plastic shell. Conventional single-stage rapid high-temperature curing (e.g., directly heating to 160°C) is not feasible. This can cause the diluent and solvent inside the conductive adhesive 300 to rapidly boil and vaporize before the initial cross-linking network forms in the resin matrix, leaving a large number of micropores inside the conductive layer. These pores not only block the conductive network formed between silver particles, resulting in a large dispersion of the equivalent series resistance, but also severely weaken the shear strength of the surface contact interface.

[0098] The stepped heating curve used in this embodiment has a first stage (80°C). The temperature is controlled near or slightly below the boiling point of most solvents, allowing the solvent to escape slowly at low resin viscosity. The second stage (150℃~170℃) provides sufficient heat energy to drive the polymer resin system to undergo a complete chemical cross-linking reaction.

[0099] To ensure consistent curing quality for different batches and volumes of plastic-cased capacitors 10 within the curing oven, the heating device in this embodiment does not employ timed constant temperature control. Instead, it incorporates a real-time curing degree integral control algorithm based on autocatalytic reaction kinetics. This algorithm dynamically calculates the real-time crosslinking state of the colloid and dynamically fine-tunes the holding time and heating rate within specified limits.

[0100] The curing of conductive adhesive 300 is essentially a thermally induced polymerization process of polymer chain segments, accompanied by exothermic and autocatalytic effects. The system calculates the real-time degree of curing of conductive adhesive 300 using the following nonlinear high-order integral model. :

[0101] in, For the current moment The cumulative degree of curing; the value range is (Right now ); The absolute temperature is measured in real time inside the curing oven, and the unit is Kelvin (K). Let be the pre-exponential factors for non-catalytic and autocatalytic reactions, respectively, with values ​​typically ranging from 1 to 2. Between these values, the value is generally provided by the supplier of conductive adhesive 300, or extracted offline by multiple linear regression at different heating rates using differential scanning calorimetry. Let be the apparent activation energies for non-catalytic and autocatalytic reactions, respectively, with values ​​ranging from 1 to 2. The results were also obtained through non-isothermal kinetic analysis of DSC experimental data; The ideal gas constant has a fixed value. ; Let be the reaction orders of the autocatalytic reaction and the non-catalytic reaction, respectively. Their sum usually satisfies the following condition: , is an empirical parameter characterizing the spatial steric hindrance effect of the resin network; The above formula is derived based on the Kamal-Sourour phenomenological dynamic model, and the integrand of the equation represents the curing reaction rate. The first term within the square brackets on the right side of the equation represents the primary reaction rate, which is dominated by temperature. The second term represents the autocatalytic acceleration effect induced by the increase of cured products. The last term... This characterizes the decay effect where the reaction rate eventually approaches zero as the concentration of unreacted substances decreases.

[0102] Direct correspondence with preparation process and experimental verification: Pre-curing stage (80) ~100 Experiments show that conductive adhesive 300 reaches its gel point (typically) upon curing. Before this point, the system remains in a liquid or semi-fluid state, which is the optimal window for venting. The control system integrates online using the above formula, and when the cumulative degree of curing is monitored... Approaching the set gel threshold And the time is When the time interval is reached, the system determines that the solvent has fully evaporated and automatically triggers the main heating program to raise the temperature to the second stage.

[0103] Full curing stage (150) ~170 ): After entering the high-temperature zone, due to A significant increase in the exponential term indicates that the autocatalytic reaction proceeds more vigorously. The curve rises sharply in an S-shape. The control system continues integral calculations until... (This indicates that over 98% cross-linking has occurred, at which point the conductive silver network is completely compressed by the tightly packed resin matrix, minimizing contact resistance), and the time falls within... Within the compliant timeframe of one hour, the system determines that complete cross-linking and curing have been achieved, and then initiates a cooling process.

[0104] The above algorithm is a typical online real-time control model. In a specific implementation scenario, the hardware architecture executing this algorithm consists of an industrial control computer (IPC), a programmable logic controller (PLC), and a multi-channel temperature control module, and its execution is based on the following: Data acquisition network: Multiple K-type or T-type thermocouples are distributed above the conveyor belt and around the heating zone inside the curing oven. The thermocouples acquire the actual temperature of the oven chamber and the plastic shell surface with a sampling period of hundreds of milliseconds. and through The converted data is then fed into the PLC.

[0105] Online integration calculation: The high-speed processor inside the PLC uses the fourth-order Runge-Kutta method or a simple Euler forward difference method to discretize and numerically integrate the above Kamal-Sourour equations, accumulating a fixed increment once per sampling period and updating the current value in real time. value.

[0106] Closed-loop negative feedback execution: The PLC will calculate the real-time... Compared with the target process threshold (such as the pre-curing period) or the complete curing period The comparison is performed. Based on the comparison deviation, the PLC outputs PID or model predictive control (MPC) commands to the solid-state relay (SSR) and thyristor power regulator of the curing oven to dynamically adjust the output power of the infrared heating tube or hot air circulation motor. This ensures at the physical equipment level that the stepped heating curve not only conforms to the temperature and time range of the claims, but also adaptively achieves the most ideal micro-crosslinking in complex heat transfer environments.

[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A plastic-cased capacitor, characterized in that, It includes a plastic shell body, a capacitor core package housed in the inner cavity of the plastic shell body, and a sealing filler for closing the opening of the plastic shell body; The plastic shell body is made of an insulating polymer material doped with laser-activated additives, and a three-dimensional metallized conductive layer is directly bonded to the surface and inner cavity wall of the plastic shell body. The positive and negative leads of the capacitor core are respectively in surface contact with the three-dimensional metallized conductive layer in the region inside the plastic shell body. The three-dimensional metallized conductive layer extends to the outside of the plastic shell body to form external surface mount pins, and there is no independent metal lead frame inside the plastic shell body.

2. A plastic-cased capacitor according to claim 1, characterized in that, The three-dimensional metallized conductive layer includes an inner wall contact pad, a conductive via, and an outer surface mounting pad; the inner wall contact pad is disposed on the inner cavity wall of the plastic shell body and is directly connected to the lead-out end of the capacitor core; the conductive via penetrates the wall thickness of the plastic shell body and electrically connects the inner wall contact pad to the outer surface mounting pad disposed on the outer bottom surface of the plastic shell body.

3. A plastic-cased capacitor according to claim 1, characterized in that, The insulating polymer material is any one of liquid crystal polymer, polyamide, or polyphenylene sulfide; the laser-activated additive is an organometallic complex, and the mass percentage of the organometallic complex in the insulating polymer material is 3% to 8%.

4. A plastic-cased capacitor according to claim 1 or 2, characterized in that, The three-dimensional metallized conductive layer is a multi-layer composite structure, which includes, from the surface of the plastic shell body outward, a metal crystal nucleus layer formed by laser activation and reduction, a chemical copper plating layer, a chemical nickel plating layer, and an anti-oxidation gold layer or an anti-oxidation tin layer.

5. A plastic-cased capacitor according to claim 2, characterized in that, The positive and negative leads of the capacitor core are fixedly connected to the inner wall contact pad by conductive silver paste or anisotropic conductive paste, and the connection surface is a flat bonding structure without leads.

6. A plastic-cased capacitor according to claim 1, characterized in that, The capacitor core is a wound solid aluminum electrolytic capacitor core or a stacked tantalum capacitor core, and the interior of the capacitor core contains a conductive polymer solid electrolyte generated by in-situ polymerization.

7. A manufacturing process for a plastic-cased capacitor, characterized in that, Includes the following steps: S100. Inject insulating polymer material particles doped with the laser activation additive into a mold, and injection mold at a preset temperature to obtain the plastic shell body with an inner cavity and a reserved through hole; S200. Using a laser beam to scan and irradiate the inner wall of the plastic shell body, the inner wall of the through hole, and the outer bottom surface according to a preset three-dimensional circuit path, so that the surface layer of the insulating polymer material in the irradiated area undergoes a physicochemical reaction and precipitates metal crystal nuclei. S300. The activated plastic shell body is placed in a chemical plating solution, and the precipitated metal crystal nuclei are used as catalysts to deposit metal, and the three-dimensional metallized conductive layer is grown on the preset three-dimensional circuit path. S400. Apply conductive adhesive to the inner wall contact pad inside the plastic shell body, push the capacitor core into the inner cavity so that its positive and negative leads are in contact with the conductive adhesive, and then heat to cure. S500. Inject fluid-like insulating resin into the opening of the plastic shell body, and degas and cure it under vacuum to form the sealing filler to complete the final encapsulation.

8. The manufacturing process of the plastic-cased capacitor according to claim 7, characterized in that, In step S200, the laser beam is an infrared laser with a wavelength of 1064nm or an ultraviolet laser with a wavelength of 355nm; the laser irradiation power is... The laser scanning speed is controlled between 1000mm / s and 4000mm / s.

9. The manufacturing process of the plastic-cased capacitor according to claim 7, characterized in that, In step S300, the electroless plating process sequentially performs electroless copper plating, electroless nickel plating, and electroless gold / tin plating; the total thickness of the formed three-dimensional metallized conductive layer is controlled between 15μm and 40μm.

10. The manufacturing process of the plastic-cased capacitor according to claim 7, characterized in that, In step S400, the heating and curing adopts a stepped temperature rise curve: first, pre-curing is carried out at an ambient temperature of 80℃~100℃ for 15~30 minutes to evaporate the solvent, and then the temperature is raised to an ambient temperature of 150℃~170℃ and held for 1~2 hours to achieve complete cross-linking and curing.